Die Tiefseegarnele Pandalus borealis im Nordostatlantik. Biologie, Bestandssituation und fischereiliche Nutzung - Schöne, Rüdiger (2000)
One of the most common decapode in the North Atlanticis the “Northern” or “Pink shrimp” Pandalus borealis(Kröyeri). Due to decreasing fish stocks and catches theshrimp fishery was intensified during most recent years.In the North-East Atlantic, a profitable fishery on thisspecies has been carried out by Norway and USSR/Russia off Norway, in the Barents Sea and offSpitsbergen for about 30 years. For the first time,Germany started a shrimp fishery with FMV “Hannover”in this area in spring/summer 1999. This article givesinformation on the biology of Pandalus borealis. A briefdescription of the problems in stock analyses, stockassessment, and the TACs (Total Allowable Catches) forthe entire North Atlantic are given. Johann Heinrich von Thünen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung = Information on Fishery research in 2010.